Peningkatan Sumberdaya Manusia Melalui Penerapan Total Quality Management - Suyitno Suyitno (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
In increasing the quality of human resources, corporate can implement total quality management (TQM), by which an employee should do a job better, more effective and more efficient in producing the products with high quality and competitive price. The research aims to identify the implementation process of TQM, and its influence toward the quality of human resources. The result showed the variables of TQM (that is, employees role, employer role, relations of employer and employees, organizational aspects, and environ employees, organization aspects, and environmental aspects) are simultaneously have a significant influence toward the quality of human resources in PR. HF Prima Malang. The organizational aspects variable is dominantly influence the corporate’s quality of human resources.